Sekolah Islam Terpadu Sebagai Ekspresi Identitas Kaum Muslim Urban - Bambang Mudjiyanto; Launa Launa; Muhammad Daffa Shilbi; Afkar Khaibar Al-Faruqi (ARIMA : Jurnal Sosial Dan Humaniora, 2024)
The increasingly materialistic dynamics of urban modernization have triggered the anxiety of most urban Muslims in deciding on the education of their children. In this materialistic era, the orientation of education has also shifted towards pragmatism that gives a small portion of religious content. This reality has made urban Muslims choose Islamic boarding schools, madrasas and modern Islamic schools that give a large portion of religion as an alternative education for their children. This qualitative study (based on Weber's social action theory and Coleman's rational choice theory) with a literature review analysis method tries to unravel the factors behind urban Muslims choosing schools with a strong touch of Islamic teachings as an alternative for education/inheritance of Islamic values for their children. The study concludes that internal factors (inheritance of religious values), external factors (influence of social environment and increasingly religious families), and performance factors (personal motives of Muslim parents) into the three dominant choices/motives.